Stress of life at the ocean's surface: Latitudinal patterns of UV sunscreens in plankton across the Atlantic. (November 2017) - Fileman, Elaine S.; White, Daniel A.; Harmer, Rachel A.; Aytan, Ülgen; Tarran, Glen A.; Smyth, Tim; Atkinson, Angus
Highlights: Highest concentration of MAAs in seston coincided with distribution of Trichodesmium . Copepods in temperate regions contained highest concentration of MAAs. MAAs in juvenile stages not detected. Zooplankton abundance and genera richness was low in the surface waters. Abstract: The near-surface layer of the ocean is a habitat in which plankton are subjected to very different stresses to those in deeper layers. These include high turbulence and illumination, allowing increased visibility to predators, and exposure to harmful UV radiation. To provide insights into stress caused by UV, we examined the occurrence of protective UV-absorbing compounds called mycosporine-like amino acids (MAAs) in seston and zooplankton along an Atlantic Meridional Transect (AMT) between 45°S and 50°N. Seston contained most MAAs per unit phytoplankton carbon in the northern Atlantic gyre and equatorial region and this coincided with distribution of the nitrogen fixing cyanobacterium Trichodesmium spp. and increased UV transparency but not irradiance. Asterina-330 was the most abundant MAA in the seston. MAAs were detected in a third of the zooplankton tested and these taxa varied greatly both in the amount and diversity of the MAAs that they contained with copepods in temperate regions containing highest concentration of MAAs. Most commonly found MAAs in zooplankton were palythine and shinorine. Juvenile copepods were found not to contain any MAAs. We determined abundance and richness of zooplankton inhabiting the top 50 cm of the ocean. Zooplankton abundance and genera richness was low in the surface waters in contrast to the dome-shaped latitudinal trend in genera richness commonly found from depth-integrated zooplankton sampling. The lack of any measurable MAA compounds in nauplii across the whole transect was concomitant with their severe (3–6-fold) reduction in nauplii densities in the near-surface layer, as compared to the underlying water column. Overall we suggest that the UV stress on life near the surface, particularly in the warmer, oligotrophic and brightly-lit low latitudes, imposes radically different pressures on zooplankton communities compared to the rest of the epipelagic.